1997
DOI: 10.1101/gr.7.5.422
|View full text |Cite
|
Sign up to set email alerts
|

An STS-Based Radiation Hybrid Map of the Human Genome

Abstract: We have constructed a physical map of the human genome by using a panel of 83 whole genome radiation hybrids (the Stanford G3 panel) in conjunction with 10,478 sequence-tagged sites (STSs) derived from random genomic DNA sequences, previously mapped genetic markers, and expressed sequences. Of these STSs, 5049 are framework markers that fall into 1766 high-confidence bins. An additional 945 STSs are indistinguishable in their map location from one or more of the framework markers. These 5994 mapped STSs have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
213
2
2

Year Published

1997
1997
2005
2005

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 309 publications
(231 citation statements)
references
References 27 publications
(31 reference statements)
13
213
2
2
Order By: Relevance
“…The sequence of the partner DNA in the treatment-related ALL did not share homology with known sequences of AF-4. Nonetheless, the closest framework marker to the AF-4 gene (24) and to the partner DNA in the treatment-related ALL was the same. These results suggest that panhandle PCR amplified either a previously uncharacterized intronic region of the AF-4 gene or, alternatively, another genomic region in close proximity to AF-4.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The sequence of the partner DNA in the treatment-related ALL did not share homology with known sequences of AF-4. Nonetheless, the closest framework marker to the AF-4 gene (24) and to the partner DNA in the treatment-related ALL was the same. These results suggest that panhandle PCR amplified either a previously uncharacterized intronic region of the AF-4 gene or, alternatively, another genomic region in close proximity to AF-4.…”
Section: Discussionmentioning
confidence: 91%
“…However, screening of radiation hybrid panel DNAs previously indicated that the nearest linked marker to the AF-4 gene was also D4S1542 (24), suggesting that the partner DNA in the treatment-related ALL was derived from either AF-4 or from a genomic sequence in close proximity to AF-4.…”
Section: Resultsmentioning
confidence: 99%
“…The Coriell Monochromosomal Panel 2 (Coriell Cell Repositories, Camden, NJ) was PCR screened with primers IPF85 and IPB83 to establish a gross chromosomal localization. A finer localization was achieved by a PCR screen with the same primers against the Stanford Human Genome Center G3 radiation hybrid panel (Stewart et al, 1997). PCR primers were also designed within putative coding regions of the genomic sequence as determined by homology to Xenopus melanopsin (primer I PF70, 5Ј-GACACCC TACATGAGC -TCGG-3Ј; primer IPB64, 5Ј-CTGTACTTGGGGTGGGTGAT-3Ј).…”
Section: Methodsmentioning
confidence: 99%
“…Each cell line was analyzed by PCR amplification and the products were resolved on 6% polyacrylamide gels and silverstained. The second approach made use of the Stanford G3 humanhamster radiation hybrid somatic cell panel (Cox et al 1990;Stewart et al 1997), which was purchased from Research Genetics (Huntsville, AL, USA). The amplification products were resolved using a denaturing 6% polyacrylamide gel on the ALFExpress sequencer (Pharmacia).…”
Section: Chromosomal Mapping Of the Six Y Microsatellite Locimentioning
confidence: 99%